A alimentação com fórmula em recém-nascidos prematuros ou com baixo peso ao nascer - Feitosa, Antonio Lucas Ferreira; Depolli, Gabriel Trevizani; Flores, Jorge Nicolás Silva; Assunção, Monica Lopes de; Santana, Maria da Conceição Carneiro Pessoa de (Distúrbios da Comunicação, 2020)
Basuki F, Hadiati DR, Turner T, McDonald S, Hakimi M. Dilute versus full-strength formula in exclusively formula-fed preterm or low birth weight infants. Cochrane Database of Systematic Reviews 2019, Issue 6. DOI: 10.1002/14651858.CD007263.pub3.